. The relationship between the serum phosphatase and tensin homolog (PTEN) and TLR4 and the severity and prognosis of neonatal sepsis : serum phosphatase and tensin homolog (PTEN) and TLR - He, Wei; Tang, Qian; Yao, Ruining (Journal of Medical Biochemistry, 2026)
Objective:To investigate the relationship between the expression of serum phosphatase and tensin homolog (PTEN) and TLR4 and the severity and prognosis of neonatal septicemia. Methods: 116 children with sepsis admitted to the neonatal department of our hospital from March 2021 to June 2023 were recruited as research subjects. According to the SOFA scoring system, children with scores of 1 to 18 were set into the mild sepsis group (n=64), children with scores from 19 to 24 were set into the severe sepsis group (n=52), and 8 patients died in the severe sepsis group (death group), 44 cases survived (survival group). During the same period, 50 newborns with normal physical examination were selected as the control group. All patient guardians signed informed consent before inclusion in the study. The inflammation level of the children was detected by enzyme-linked immunosorbent assay and automated blood cell counter. The serum PTEN and TLR4 levels of the children were tested by enzyme-linked immunosorbent assay. Comparing the inflammation levels between the death group and the survival group in children with severe sepsis. The serum PTEN and TLR4 levels of children with severe sepsis were compared between the death group and the survival group. The correlation between PTEN, TLR4 and inflammatory indicators PCT, CRP, HBP, and WBC was analyzed by Pearson correlation. The value of biomarkers on the condition and prognosis of children was analyzed through ROC curves. Results: The levels of PCT, CRP, HBP and WBC in the severe sepsis group and mild sepsis group were higher than control group (P
Keywords: Neonatal sepsis; serum PTEN and TLR4 expression; severity; prognosis